Hubungan Kecemasan dengan Prokrastinasi Akademik Pada Siswa Di SMA Al Washliyah 3 Medan - Nur Azizah; Annawati Dewi Purba (Universitas Medan Area, 2023)
This study aims to examine the correlation between anxiety and academic procrastination in students at private high school Al Washliyah 3 Medan. The scale used in this study is the anxiety scale and the procrastination scale where the subjects in this study were private high school students Al Washliyah 3 Medan who found 61 students. The data analysis method used in this study is Product Moment correlation, so the following results can be obtained: there is a significant positive correlation between anxiety and academic procrastination. This result is evidenced by the correlation coefficient rxy = 0.409; P = 0.000 0.05, that anxiety about academic procrastination is 16.7%. From these results it is known that there are still 83.3% of other factors of academic procrastination that are not explained in the study and are not seen in this study. Students have high anxiety that with empirical mean = 133.33 hypothetical mean = 93 where the second difference exceeds SD number = 15.344 and students' academic procrastination is high with empirical mean 129.70 hypothetical mean = 102 where the difference between the two means exceeds the number SD = 15,920 . From the results of this study, the proposed hypothesis is accepted.